2015
DOI: 10.1002/mus.24686
|View full text |Cite
|
Sign up to set email alerts
|

Heat‐Stress effects on the myosin heavy chain phenotype of rat soleus fibers during the early stages of regeneration

Abstract: The results indicate that heat stress accelerates fast-to-slow MyHC phenotype conversion in regenerating fibers via activation of satellite cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…Our results show that exposure to HT immediately after and for 4 consecutive days after a maximal bout of eccentric exercise in humans hastens recovery of fatigue resistance and tends to reduce perceived soreness. These findings are in line with a growing body of literature supporting a beneficial impact of HT on recovery after noninjurious exercise (8) as well as severe muscle injuries (19,32,33,44,48). Additional studies are warranted to determine whether repeated exposure to local HT amplifies the skeletal muscle adaptations to exercise training in humans.…”
Section: Discussionsupporting
confidence: 84%
“…Our results show that exposure to HT immediately after and for 4 consecutive days after a maximal bout of eccentric exercise in humans hastens recovery of fatigue resistance and tends to reduce perceived soreness. These findings are in line with a growing body of literature supporting a beneficial impact of HT on recovery after noninjurious exercise (8) as well as severe muscle injuries (19,32,33,44,48). Additional studies are warranted to determine whether repeated exposure to local HT amplifies the skeletal muscle adaptations to exercise training in humans.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, hyperthermal therapy has attracted increasing attention in the fields of tissue engineering and cancer chemo-therapeutics due to its potential to modify the extracellular microenvironment, and thus regulate localized tissue responses including immunological reaction, tissue perfusion, and tissue oxygenation [4, 5]. Although controlled thermal delivery of heat has shown some beneficial effects on myogenesis during skeletal muscle repair in both in vitro [68] and in vivo studies [911], the detailed and coordinated effects of thermal treatment on muscle regeneration remain under characterized, limiting the development of a tailored hyperthermia treatment protocol for muscle regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Myofibrillogenesis, the development of the myofibril during myogenesis, plays a critical role in controlling the contractile strength of skeletal muscles [14, 15]. Recently, Yamaguchi et al [6] and Oishi et al [9] reported a fast-to-slow fiber-type shift in myotubes or myofibers during myogenesis in their in vitro and in vivo studies, respectively. Yet, their work solely focused on analyzing the expressions of myosin heavy chains.…”
Section: Introductionmentioning
confidence: 99%
“…Yamaguchi et al (40) also reported that continuous heat stress (39°C for 6 h) caused differentiation and a fast-to-slow fiber-type transition in mammalian myoblasts. Similarly, Oishi et al (25) reported that intermittent application of heat stress (42°C for 30 min on alternating days) to injured rat soleus muscle promoted a fast-to-slow transformation of MyHC phenotypes at an early phase of regeneration after injury. In agreement with these findings, the present study revealed that the timing of the disappearance of MyHC neo and IIb isoforms in regenerating soleus muscles was accelerated by heat stress at the whole-muscle level (Fig.…”
Section: Discussionmentioning
confidence: 89%